Association between Poor Ergophthalmologic Practices and Computer Vision Syndrome among University Administrative Staff in Ghana. - Boadi-Kusi, Samuel Bert; Abu, Sampson Listowell; Acheampong, George Oppong; Adueming, Peter Osei-Wusu; Abu, Emmanuel Kwasi (Journal of Environmental & Public Health, 2020)
Aim: The aim of this study was to assess the prevalence of computer vision syndrome (CVS) and its associated ergonomic factors among university administrative staff in Ghana.Methods: A cross-sectional survey was conducted among 200 administrative staff of the University of Cape Coast. The procedure included a self-administered questionnaire, comprehensive ocular health examination, and assessment of computer workstation and lighting conditions. The prevalence of CVS among the subjects and the association between CVS and ergonomic practices were determined.Results: The mean age of the study sample was 31.0 ± 4.7 years, and the majority were males (56.0%). The prevalence of CVS was among 103 (51.5%)participants. Over a third of the respondents used computers for 6 or more hours daily. Significant association was found between CVS and poor ergonomic practices (χ = 15.175, p = 0.001).Conclusion: In addition to poor ergonomic office setup, university administrative staff spend several hours behind computer screens leading to the development of CVS. Increased awareness of CVS and adherence to recommended ergonomic practices are necessary to reduce the prevalence of CVS and ultimately enhance work satisfaction and productivity.